El suero de neonatos de Clelia clelia (Serpentes: Colubridae) neutraliza la acción hemorrágica del veneno de Bothrops asper (Serpentes: Viperidae). - Lomonte, Bruno (1989)
The ability of serum from nine newbom specimens of Clelia clelia (Colubridae) to neutralize hernorrhagic action of Bothrops asper venom was tested. All serum samples neutralized completely the hernorrhagic effect of the venom in mice. This finding shows that the neutralizing ability of C. clelia serum towards the hemorrhagic activity of B. asper venom is innate.